2019
DOI: 10.1055/a-0985-4373
|View full text |Cite
|
Sign up to set email alerts
|

Oral Contraceptive Use does not Negatively Affect Body Composition and Strength Adaptations in Trained Women

Abstract: The purpose was to analyze the influence of oral contraceptive use on body composition and strength levels in trained women. Twenty-three resistance-trained women participated in this study (age=27.4±3.4 years; fat mass=28.0±5.0%; BMI=22.9±2.7 kg∙m-2). Subjects performed an 8-week non-linear resistance-training program. Participants were assigned to either a group that consumed oral contraceptives (n=12, OC) or to a group that did not consume (n=11, NOC). Changes in body composition were measured by dual energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…In line, a new study conducted on resistance-trained women demonstrated after 8 weeks of resistance training, no significant difference in FFM between OC-users and nonusers. Nevertheless, a significant increase from pre to post was only observed in the young women using OCs (32). Noteworthy, the OC-users in both studies used a mix of OC types (45).…”
Section: Discussionmentioning
confidence: 90%
“…In line, a new study conducted on resistance-trained women demonstrated after 8 weeks of resistance training, no significant difference in FFM between OC-users and nonusers. Nevertheless, a significant increase from pre to post was only observed in the young women using OCs (32). Noteworthy, the OC-users in both studies used a mix of OC types (45).…”
Section: Discussionmentioning
confidence: 90%
“…Older research found that COC use altered muscular strength [ 227 , 228 ] and an inhibiting effect on protein synthesis [ 229 ]. More recent papers, however, showed no difference in maximal force-generating capacity, jumping, or hopping with COC use [ 18 , 19 , 31 , 230 ] and did not suggest that COC use affects strength or endurance in response to strength-only or combined strength/endurance training [ 224 , 231 , 232 ]. However, further research is necessary to determine whether COC androgenicity plays a significant role in strength development [ 224 ].…”
Section: Possible Mechanisms: Performance and Health Risksmentioning
confidence: 99%
“…These findings indicate that OC use does not affect maximal isometric muscle strength, which is consistent with the findings of Nichols et al that OC use does not negatively affect muscle strength gains after a 12-week free-weight strength training program because it prevents fluctuations in other anabolic hormones during the menstrual cycle [ 50 ]. Romance et al [ 51 ] analyzed the influence of OC use on strength after 8 weeks of resistance training and found no differences in muscle strength gains between their non-OC and OC groups. Furthermore, Wikstrom-Frisen et al found no significant differences in strength, squat jump ability, or isokinetic peak torque between women who used OCs and those who did not [ 52 ], while Nichols et al found no differences in isokinetic torque and maximum strength gain between female student athletes who used OCs and those who did not [ 22 ].…”
Section: Discussionmentioning
confidence: 99%